Application of information characteristics in models of driver’s perception of road conditions - Кульбашная, Надежда Ивановна; Линник, Ирина Эдуардовна (Eastern-European Journal of Enterprise Technologies, 2015)
Further development of the information theory in the model of driver’s perception of road conditions was proposed. It is assumed that there is a definite dynamic relationship between the relative organization of the driver’s perception field and the relative organization of the driver’s interaction with the environment, which in turn is determined by the variability of motion speeds. Therefore, the first step in the analysis is developing a dynamic model of the influence of the relative organization of the driver’s perception field on motion speeds. Therefore, the process of directional formation of the motion medium by regulating the motion speeds is considered in the proposed model as a dynamic process of changing the relative organization of the driver’s perception field. For this purpose, the transfer function of the driver, in which the function of the relative organization of the driver’s perception field is an input characteristic and the speed change – an output parameter is used. Conversion of the transfer function is carried out on the assumption that the driver’s reaction to a periodic change in the relative organization of the driver’s perception field can be represented as a sequence of rectangular pulses. The transfer function is solved using the Laplace transform.